Examining Ethical Journalism and Media Self-Regulation in Nepal - Pant, Laxman Datt; Nizam, Mohd Nashriq (Journal of Advanced Academic Research, 2026)
Ethical journalism and effective mechanisms of media self-regulation are considered fundamental to sustaining public trust and media credibility. In Nepal, despite the practice of the Journalists’ Code of Conduct enforced by the Press Council Nepal (PCN), key concerns remain regarding violations of such codes alongside declining media professionalism, and weak complaints handling mechanisms both at the PCN and within newsrooms. This article presents a systematic literature review observing the challenges to ethical journalism in Nepal, with a particular focus on self-regulation among journalists and the efficacy of the Journalists’ Code of Conduct. Based on the Social Responsibility Theory of the press, this review covers global and Nepal-focused scholarly literature to identify professional and regulatory elements that undermine ethical journalistic practice. Following a systematic review protocol, peer-reviewed articles, doctoral dissertations and institutional reports were analyzed using inductive thematic synthesis. The review finds that while self-regulation is widely endorsed as a normative ideal, its efficacy in Nepal is constrained by weak enforcement capacity, political interference, absence of newsroom-level accountability systems and low public awareness of complaint-handling at the PCN and within media platforms.  A significant gap between normative ethical standards and everyday journalistic practice is evident. The review concludes by proposing context-sensitive approaches to strengthen media self-regulation in Nepal, improve media accountability, and restore journalistic practice following the principles of social responsibility and professional standards. This review is the first scholarly output of the doctoral study which forms a conceptual foundation for succeeding pragmatic study.